K2CO3-Mediated Intramolecular Oxa-Michael Cyclization of α,β-Unsaturated Ketoximes: Synthesis of Densely Arene-Substituted 2-Isoxazolines Bearing a Quaternary Center - Jat, Ram Singh; Kothapalli, Raveendrababu; Bhanuchandra, M. (Synthesis, 2024)
An efficient K2CO3-mediated intramolecular oxa-Michael cyclization of β,β-diarylated α,β-unsaturated ketoximes is described. This methodology allows access to arene-rich 2-isoxazoline derivatives bearing a quaternary center in excellent yields with an operationally simple experimental procedure. Deuterium-scrambling experiments were carried out to shed light on the reaction pathway. To demonstrate the synthetic utility of the method, a large-scale synthesis and Ullmann-type C–N bond-formation reaction between pyrazole and dibrominated isoxazoline was performed.
Keywords: 2-isoxazolines; α,β-unsaturated ketoximes; oxa-Michael cyclization; Ullmann-type amination; base-mediated reaction